On Baer-Shemetkov’s decomposition in modules and related topics - Kirichenko, V.V.; Kurdachenko, L.A.; Pypka, A.A.; Subbotin, I.Ya. (Algebra and Discrete Mathematics, 2013)
This article is dedicated to the memory of an outstanding algebraist Leonid A. Shemetkov. His ideas and results not only shaped modern soluble finite group theory, but significantly influenced other branches of algebra. In this article, we traced the influence of L.A. Shemetkov's ideas on some areas of modules theory and infinite groups theory.